Modeling of the Impact of the Credibility of the Destination Endorser on the Place Attachment of Potential Tourists - Shang, Ziye; Luo, Jian Ming (Frontiers in Psychology, 2021)
Place attachment has been identified as effective marketing strength to enhance destination competitiveness. However, little research explored the formation mechanism of potential tourists’ place attachment and the role of celebrity endorser. This study aims to identify the influence mechanism of endorser’s credibility on place attachment. Various theories from different research fields were introduced to explore the mediating effect of destination attitude, para-social relationships and destination source credibility between endorser credibility and potential tourists’ place attachment. The famous destination endorser in China, Tenzin, was chosen as the case. A quantitative method was adopted. The research model was examined by a survey sampling size of 367 respondents. The covariance-based structural equation model analysis revealed that the endorser’s credibility exerts a positive influence on potential tourists’ destination attitude, para-social relationship with the endorser and destination source credibility. These three constructs have a positive effect on their place attachment. Result showed that endorser’s credibility has a significant indirect influence on place attachment. This study extends the current literature of forming potential tourist’s place attachment from the destination endorser’s personal characteristics perspective. The findings shed light on how the endorser’s credibility could form place attachment through enhancing potential tourists’ destination attitude, credibility, and para-social relationships. This study provides several practical implications for destination marketing.